Peran Strategis Public Relations di Perguruan Tinggi - Ike Devi Sulistyaningtyas (FISIP Universitas Atma Jaya Yogyakarta, 2007)
Abstracts: Public Relations emphasizes in building and maintaining a relationship between an organization and its public. It is applied also for a higher education institution or university. Nowadays, public relations in higher education institution become an integral part of the management team. It must contribute to achieve organizational goals and demonstrate an organizational accountability identified by measurable result. Synergy and cooperation are the strategic way to reach good relationship and reputation.